Sonic ethnography Identity, heritage and creative research practice in Basilicata, southern Italy - Ferrarini, Lorenzo (Manchester University Press, 2020)
Sonic ethnography explores the role of sound-making and listening practices in the formation of local identities in the southern Italian region of Basilicata. The book uses a combination of text, photography and sound recording to investigate soundful cultural performances such as tree rituals, carnivals, pilgrimages, events promoting cultural heritage and more informal musical performances. Its approach demonstrates how in the acoustic domain tradition is made and disrupted, power struggles take place and acoustic communities are momentarily brought together in shared temporality and space. This book underlines how an attention to sound-making, recording and listening practices can bring innovative contributions to the ethnography of an area that has been studied by Italian and foreign scholars since the 1950s. The approaches of the classic anthropological scholarship on the region have become one of the forces at play in a complex field where discourses on a traditional past, politics of heritage and transnational diasporic communities interact. The book's argument is carried forward not just by textual means, but also through the inclusion of six 'sound-chapters', that is, compositions of sound recordings themed so as to interact with the topic of the corresponding textual chapter, and through a large number of colour photographs. Two methodological chapters, respectively about doing research in sound and on photo-ethnography, explain the authors' approach to field research and to the making of the book.